Convergent Neural Correlates of Empathy and Anxiety During Socioemotional Processing - Knight, Lindsay K.; Stoica, Teodora; Fogleman, Nicholas D.; Depue, Brendan E. (Frontiers in Human Neuroscience, 2019)
Empathy is characterized by the ability to understand and share an emotional experience with another person and is closely tied to compassion and concern for others. Consequently, this increased emotional awareness and sensitivity may also be related to increased anxiety. Taken from another perspective, higher general anxiety may translate into increased concern for others, or concern for how one’s actions might affect others, and therefore may be linked to increased empathy. Furthermore, self-reflection is positively related to perspective-taking and empathic concern, while rumination is closely tied to anxiety, thus providing an additional connecting point between empathy and anxiety through enhanced internally generated thought. While previous literature suggests a relationship between empathy and anxiety, this has yet to be empirically studied using neuroimaging tools aimed at investigating the underlying neural correlates that may support these convergent responses. We therefore conducted an fMRI study (N=49) in which participants viewed fearful and neutral human faces and rated how the faces made them feel, to promote introspection. Participants also completed questionnaires assessing empathy (TEQ), trait anxiety (STAI), worry (PSWQ) and rumination (RRS). Behaviorally, empathy positively correlated with worry, worry and rumination positively correlated with anxiety, and significant indirect relationships were found between empathy and anxiety through worry and rumination. Using the neuroimaging face processing task as a backdrop on which the neurobiological mechanisms of empathy and anxiety may interact, regressions of questionnaires with brain activations revealed that empathy related to activation in the temporoparietal junction (TPJ), anxiety related to bilateral insula activation, and worry related to medial prefrontal cortex activation, while rumination showed increased engagement of all three aforementioned regions. Functional connectivity analyses showed increased communication between the left amygdala and insula related to higher empathy, worry and rumination. Finally, whole-brain analysis using median split groups from questionnaires revealed that the lower halves of anxiety, worry and rumination exhibited increased activation in top-down attentional networks. In sum, empathy, worry and rumination related to enhanced bottom-up processing, while worry, rumination and anxiety exhibited decreased top-down attentional control, suggesting an indirect relationship between empathy and anxiety through the ruminative tendencies of worry.